2004
DOI: 10.1111/j.1440-1746.2004.03428.x
|View full text |Cite
|
Sign up to set email alerts
|

Four years of lamivudine treatment in Chinese patients with chronic hepatitis B

Abstract: Despite the emergence of YMDD-variant HBV, Chinese patients showed increased HBeAg seroconversion and improvement in ALT levels with an increased duration of treatment with lamivudine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
172
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(177 citation statements)
references
References 27 publications
4
172
1
Order By: Relevance
“…It was observed in other studies that genotypic resistance to LAM increases from 15 to 30% after 1 year of treatment to 70% after 5 years of treatment [2,[22][23][24]. It is almost similar for longer duration but was less for shorter duration because we have studied VBT, whereas others had studied genotypic resistance.…”
Section: Discussionmentioning
confidence: 71%
“…It was observed in other studies that genotypic resistance to LAM increases from 15 to 30% after 1 year of treatment to 70% after 5 years of treatment [2,[22][23][24]. It is almost similar for longer duration but was less for shorter duration because we have studied VBT, whereas others had studied genotypic resistance.…”
Section: Discussionmentioning
confidence: 71%
“…Lamivudine has demonstrated efficacy and long-term safety and was shown to result in histologic improvement when administered for up to 3 years [16,18,19]. However, resistance to lamivudine emerges at a rate of approximately 20% per year and is found in approximately 70% of patients after 4 years of therapy [20,21]. The emergence of lamivudine resistance may be associated with increases in HBV DNA and alanine aminotransferase (ALT) levels, and loss of histologic response [16,18,22].…”
Section: Introductionmentioning
confidence: 99%
“…Although efficacious and well tolerated, lamivudine therapy is associated with a high rate of viral resistance [6][7][8][9] that may reach up to 70% after 4 years of treatment [6,10,11]. While some studies have suggested that continuing lamivudine in the presence of resistance may promote HBeAg seroconversion and maintain lower alanine aminotransferase (ALT) and HBV DNA levels than were present at baseline [11][12][13], accumulated evidence now shows that there is no benefit to continuing lamivudine in this population.…”
Section: Introductionmentioning
confidence: 99%
“…While some studies have suggested that continuing lamivudine in the presence of resistance may promote HBeAg seroconversion and maintain lower alanine aminotransferase (ALT) and HBV DNA levels than were present at baseline [11][12][13], accumulated evidence now shows that there is no benefit to continuing lamivudine in this population. Patients with lamivudine-resistant HBV who continue to receive lamivudine have been shown to experience increases in viral load [6,10,[14][15][16], hepatic flares that may lead to decompensation [15,[17][18][19], and reduction or reversal of histologic improvement [20]. These observations highlight the need for a treatment alternative for chronic hepatitis B patients who have developed lamivudine resistance.…”
Section: Introductionmentioning
confidence: 99%